Growth of melon cultivated in coconut fiber under different concentrations of nutrient solution - Cosme, Christiano Rebouças; Dias, Nildo da Silva; Silva, Karen Mariany Pereira; Fonteles, John Lenon Vasconcelos; Gurgel, Marcelo Tavares; Fernandes, Cleyton dos Santos (Comunicata Scientiae, 2018)
To evaluate the effects of applying different concentrations of the nutrient solution macronutrients in growth of melon cultivated in coconut fiber it was conducted this experiment uses the ‘Galia’ melon (Cucumis melo L., hybrid Babilonia RZ F1). The experimental design was a randomized blocks utilizing five treatments, which corresponded to different concentrations of macronutrients in nutritive solutions (corresponding to different levels of nutrient solution macronutrients) based on the standard solution for the melon proposed by Furlani: 100 (control), 75, 50, 25, and 12.5%, applied in five replications. The concentration of 50% provided higher production of dry matter of the aerial part and leaf area. The absolute aerial part growth rate showed different tendencies for levels being that concentration of 50% produced the best results. The relative growth rate of the aerial part and assimilation rate of the aerial part decrease with time for all concentrations of the nutrient solutions tested.